Analisis Efektivitas Dan Kontribusi Penerimaan Uang Kuliah Tunggal Terhadap Pendapatan Blu di Universitas Negeri Malang - Hardi Sona Kurniawan; Sri Hadiati; Jose Rizal Joesoef (Warta Pendidikan | e-Journal, 2021)
This study discusses the problem of effectiveness and contribution of single tuition fees at the State University of Malang to Blu's income. As a college that accepts student attendance every year, State University of Malang does so with a high degree of effectiveness in admitting a single tuition fee. From the results of this study, data obtained that, 1) The level of effectiveness of the realization of UKT acceptance in the work unit at the State University of Malang as a whole for three years was in a very effective condition Overall, the work unit was able to realize UKT revenues exceeding the existing budget target, with an average achievement level in 2016 of 180.89%, the average achievement level in 2017 was 194.93%, the average achievement level in 2018 was 209.49%, and the average level of achievement from 2016 to 2018 is 195.11%. 2) The contribution rate of UKT acceptance for all work units for three years, the largest contribution from the Faculty of Economics (FE) which was able to contribute 12.06% of UKT admissions, followed by the Faculty of Engineering (FT). This work unit was able to contribute more than 10% of UKT revenue. The next UKT acceptance contribution under 10% was given by the Faculty of Letters (FS), the Faculty of Education (FIP), the Faculty of Mathematics and Natural Sciences (FMIPA), the Faculty of Social Sciences (FIS), the Faculty of Sport Sciences (FIK) and the Faculty of Psychology Education ( FPPsi).